2021
DOI: 10.1177/19418744211021221
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Cerebellitis Presenting With Ataxia: A Case Report

Abstract: We report a case of a woman with a history of systemic lupus erythematosus who developed persistent ataxia and was diagnosis with lupus cerebellitis. Magnetic resonance imaging of the brain showed T2/FLAIR signal hyperintensity within the cerebellar vermis without mass effect. The patient’s condition improved with pulse IV methylprednisolone. This case highlights unique imaging findings within the cerebellum, our diagnostic and treatment regimen, and compares this case to previous literature on similar cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…All of the patients were female and ranged in age from 15 to 52. Various forms and frequency rates of cerebellar involvement were reported in these studies, including cerebellar atrophy (n = 9), no imaging finding (n = 8), an abnormal signal in the cerebellar hemispheres (n = 5), solitary lesion in the dorsal part of the junction between medulla and pons (n=1), a hyperintensity involving vermis (n = 2), a hyperintensity involving paravermis (n = 1), a hyperintense area in the peduncles (n = 1), and an isolated lesion in the brainstem (n = 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. One study had not reported its imaging finding [18].…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients were female and ranged in age from 15 to 52. Various forms and frequency rates of cerebellar involvement were reported in these studies, including cerebellar atrophy (n = 9), no imaging finding (n = 8), an abnormal signal in the cerebellar hemispheres (n = 5), solitary lesion in the dorsal part of the junction between medulla and pons (n=1), a hyperintensity involving vermis (n = 2), a hyperintensity involving paravermis (n = 1), a hyperintense area in the peduncles (n = 1), and an isolated lesion in the brainstem (n = 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. One study had not reported its imaging finding [18].…”
Section: Discussionmentioning
confidence: 99%